Performance analysis of multilayer multicast MANET CRN based on steiner minimal tree algorithm - Basma Nazar Nadhim; Sarab Kamal Mahmood (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
In this study, the multicast mobile ad hoc (MANET) CRN has been developed, which involves multi-hop and multilayer consideration and Steiner minimal tree (SMT) algorithm is employed as the router protocol. To enhance the network performance with regards to throughput and packet delivery rate (PDR), as channel assignment scheme, the probability of success (POS) is employed that accounts for the channel availability and the time needed for transmission when selecting the best channel from the numerous available channels for data transmission from the source to all destinations nodes effectively. Within Rayleigh fading channels under various network parameters, a comparison is done for the performance of SMT multicast (MANET) CRN with POS scheme versus maximum data rate (MDR), maximum average spectrum availability (MASA) and random channel assignment schemes. Based on the simulation results, the SMT multicast (MANET) CRN with POS scheme was seen to demonstrate the best performance versus other schemes. Also the results proved that the throughput and PDR performance are improved as the number the primary channels and the channel’s bandwidth increased while dropped as the value of packet size D increased. The network’s performance grew with rise in the value of idle probability (P_I) since the primary user’s (PU) traffic load is low when the value of P_I is high.